Bispecific Antibodies in the Treatment of Hematologic Malignancies - Duell, Johannes (Clin Pharmacol Ther, 2019)
Monoclonal antibody therapies are an important approach for the treatment of hematologic malignancies, but typically show low single‐agent activity. Bispecific antibodies, however, redirect immune cells to the tumor for subsequent lysis, and preclinical and accruing clinical data support single‐agent efficacy of these agents in hematologic malignancies, presaging an exciting era in the development of novel bispecific formats. This review discusses recent developments in this area, highlighting the challenges in delivering effective immunotherapies for patients.